Peran Dinas Pemberdayaan Masyarakat dan Gampong Dalam Menuju Desa Mandiri Melalui Progam BUMDes Kabupaten Aceh Barat - Albilal Masria; Najamudin (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study discusses the role of the Community and Gampong Empowerment Service in Towards an Independent Village through the BUMDes Program in West Aceh Regency. This research shows that in getting to an independent village the village must be able to utilize existing resources in the village, manage the arrangement and development of assets in the village appropriately, the village is able to be active in community institutions and in the community environment, the availability of funds or village budgets for managing various activities, both in terms of empowerment and empowerment of village development, and supporting facilities in the village to support the village economy. With this, it is hoped that the creation of Village-Owned Enterprises (BUMDes) can become the foundation for villages in strengthening the village economy and prospering the village community in West Aceh, and also the village is able to manage the natural resources in the village. the obstacle towards independent villages in West Aceh is the weakness of the Quality of Human Resources (HR) in the village apparatus so that it becomes a very influential obstacle to village budget management which has an impact on preventing community poverty which has not been significant and has not been resolved.